2012
DOI: 10.2310/7750.2011.11015
|View full text |Cite
|
Sign up to set email alerts
|

Local Infiltrative Anesthetic Effect of Tramadol Compared to Lidocaine for Excision of Cutaneous Lesions: Pilot Randomized, Double-Blind Clinical Study

Abstract: Background: In this double-blind, randomized study, the efficacy of tramadol, an atypical opioid, was tested versus lidocaine in excision of cutaneous lesions of the face. Methods: Eighty-eight patients were randomly assigned to receive either 2 mg/kg tramadol 2% plus adrenaline 1:200,000 (group T, n = 46) or 3 mg/kg lidocaine 2% plus adrenaline 1:200,000 (group L, n = 42) for excision of cutaneous lesions. Pain at the injection site, 2 and 20 minutes postinjection and 3, 6, and 12 hours postoperatively, was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…It modulates the inhibitory descending pathways and has a good analgesic efficacy combined with minor side effects. Furthermore, tramadol produces only mild sedative effects and it is inexpensive [8].…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…It modulates the inhibitory descending pathways and has a good analgesic efficacy combined with minor side effects. Furthermore, tramadol produces only mild sedative effects and it is inexpensive [8].…”
Section: Open Accessmentioning
confidence: 99%
“…It will be necessary to investigate whether this state of agitation is caused by a local irritating action [8,18,21] or a systemic effect of the drug [22].…”
Section: Plos Onementioning
confidence: 99%
“…In a similar way, a study observed that just 1 patient had dizziness in the lidocaine group while 3 patients experienced nausea and dizziness among a group of 50 patients receiving the epinephrine-free tramadol. [ 11 ] These investigations all demonstrated that there is no discernible difference in the negative effects. All these side effects were noted in both groups in the current trial, but there was no discernible difference between the groups in terms of side effects.…”
Section: Discussionmentioning
confidence: 93%
“…Since it was first reported as displaying local anaesthetic properties in 1998 ( Pang et al, 1998 ), tramadol has been established in the literature as an effective local anaesthetic agent in medicine and dentistry including: as a perioperative wound infiltration agent for post-operative pain management in caesarean section surgery ( Behdad et al, 2013 , Demiraran et al, 2013 ; Jabalameli et al, 2012 ; Sahmeddini et al, 2017 ), lumbar discectomy surgery ( Mitra et al, 2017 , Ozyilmaz et al, 2012 ), and paediatric tonsillectomy surgery ( Akkaya et al, 2009 , Heiba et al, 2012 , Honarmand et al, 2013 , Ugur et al, 2013 ), for infraorbital nerve blocks following nasal surgery ( Cekic et al, 2013 ), as an axillary plexus blockade adjunct ( Kapral et al, 1999 , Robaux et al, 2004 ), for use in paediatric circumcision ( Kargi et al, 2010 ), tendon repair surgery ( Kargi et al, 2008 ), plastic skin lesion excision surgery ( Altunkaya et al, 2003 , Altunkaya et al, 2004 , Kakagia et al, 2012 ) and oral surgery ( Al-Haideri, 2013 , Ceccheti et al, 2014 , Ege et al, 2020 , Gönül et al, 2015 , Iqbal and Shetty, 2019 , Isiordia-Espinoza et al, 2011 , Jendi et al, 2019 , Khan et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The lack of widespread adoption of tramadol as an alternative local anaesthetic agent in clinical practice is likely due to the excellent safety, efficacy and established history of use of traditional amide-based local anaesthetics. Tramadol has however been associated with requiring less post-operative analgesia requirement ( Altunkaya et al, 2004 , Cekic et al, 2013 , Demiraran et al, 2013 , Heiba et al, 2012 ; ( Jabalameli et al, 2012 ) Kakagia et al, 2012 , Kargi et al, 2008 , Kargi et al, 2010 , Mitra et al, 2017 , Ozyilmaz et al, 2012 , Robaux et al, 2004 , Ugur et al, 2013 , Vahabi et al, 2011 ), lower post-operative pain scores ( Cekic et al, 2013 , Demiraran et al, 2013 , Heiba et al, 2012 ; ( Jabalameli et al, 2012 ) Kakagia et al, 2012 , Sahmeddini et al, 2017 , Ugur et al, 2013 ), prolonged analgesic and anaesthetic effects ( Behdad et al, 2013 , Cekic et al, 2013 , Kapral et al, 1999 , Robaux et al, 2004 ), and delaying the time to the first analgesia post-surgery ( Altunkaya et al, 2004 , Mitra et al, 2017 , Ozyilmaz et al, 2012 ) when compared to conventional local anaesthetics. To date, no study has primarily reviewed the prevalence of local and systemic adverse effects of tramadol when used as a local anaesthetic in the oral environment.…”
Section: Introductionmentioning
confidence: 99%